2018
DOI: 10.3390/molecules23061494
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Triterpenes from Salacia crassifolia and Metabolite Profiling of Celastraceae Species

Abstract: The new pentacyclic triterpene 11β-hydroxypristimerin (1), along with the known metabolites pristimerin (2), 6-oxopristimerol (3) and vitideasin (4), were isolated from a Salacia crassifolia root wood extract, following a bioassay-guided fractionation approach. Both the extract and the purified triterpenes displayed pronounced cytotoxic activity against human cancer cell lines. The NCI-60 cell line screen revealed that compound 2 was the most active, with a mean GI50 of 0.17 μM, while compound 1 had a mean GI5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…Another assay showed the cytotoxic potential of pristimerin ( 26 ) against HL-60 (IC 50 = 0.2 µM) and MCF7 (breast adenocarcinoma) (IC 50 = 0.4 µM) cell lines [77]. Recently, the NCI-60 cell line screen revealed that pristimerin ( 26 ) was active against UO-31 (renal carcinoma), T-47D (breast cancer), and A549 (non-small-cell lung cancer) human tumor cell lines with individual half maximal inhibition of cell proliferation (GI 50 ) values ranging from 0.12 µM to 1.2 µM [78]; therefore, pristimerin ( 26 ) would deserve further in vivo evaluation. Macrocarpine A ( 32 ), macrocarpine B ( 33 ), macrocarpine C ( 34 ), and macrocarpine D ( 35 ) were shown to be active against P-388D1 (mouse lymphoma), A-549 (human lung carcinoma), HT-29 (human colon carcinoma), and MEL-28 (human melanoma) cells with IC 50 ranging between 0.4 and 5.2 µM [24], whereas 28-hydroxyfriedelane-1,3-dione ( 22 ) was inactive against the same panel of cancer cell lines [16], but a positive control was missing in both studies.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Another assay showed the cytotoxic potential of pristimerin ( 26 ) against HL-60 (IC 50 = 0.2 µM) and MCF7 (breast adenocarcinoma) (IC 50 = 0.4 µM) cell lines [77]. Recently, the NCI-60 cell line screen revealed that pristimerin ( 26 ) was active against UO-31 (renal carcinoma), T-47D (breast cancer), and A549 (non-small-cell lung cancer) human tumor cell lines with individual half maximal inhibition of cell proliferation (GI 50 ) values ranging from 0.12 µM to 1.2 µM [78]; therefore, pristimerin ( 26 ) would deserve further in vivo evaluation. Macrocarpine A ( 32 ), macrocarpine B ( 33 ), macrocarpine C ( 34 ), and macrocarpine D ( 35 ) were shown to be active against P-388D1 (mouse lymphoma), A-549 (human lung carcinoma), HT-29 (human colon carcinoma), and MEL-28 (human melanoma) cells with IC 50 ranging between 0.4 and 5.2 µM [24], whereas 28-hydroxyfriedelane-1,3-dione ( 22 ) was inactive against the same panel of cancer cell lines [16], but a positive control was missing in both studies.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…The NCI continuously improved the screening systems and in the 1990s a panel of 60 human cancer cell lines was established, representing nine major tissue types (brain, blood and bone marrow, breast, colon, kidney, lung, ovary, prostate and skin). Over the last decades, compounds submitted by investigators have been screened against this NCI-60 panel to determine their growth inhibition effect [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The extract and the isolated PCTT displayed significant cytotoxic activity against the human cancer cell lines tested. 20 Pristimerin was also isolated from S. reticulata, 21 S. kraussi 14 and S. amplifolia 22 species, and inhibited the growth of several cancer cell types such as breast, prostate, pancreas and multiple myeloma tumors. 23 The present work describes further studies on S. crassifolia roots.…”
Section: Introductionmentioning
confidence: 99%